A low-silver-content solar cell low-temperature sintering HJT silver paste and preparation method thereof

By combining modified silver-coated copper powder and graphene, the electrode defects caused by silver powder shrinkage in silver paste were solved, achieving low-cost and high-efficiency photoelectric conversion.

CN116936159BActive Publication Date: 2025-01-07NANTONG T SUN NEW ENERGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310951064.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-01-07
Estimated Expiration
2043-07-31

AI Technical Summary

Technical Problem

The reduced silver content in existing HJT silver paste leads to silver powder shrinkage, resulting in cracks and holes in the electrodes, increased resistance, and reduced photoelectric conversion efficiency.

Method used

Modified silver-coated copper powder and modified graphene are used. The surface of the silver-coated copper powder is modified by a phenolic hydroxysilane coupling agent and then doped with modified graphene to form a uniform film layer, thereby reducing resistance and improving conductivity.

Benefits of technology

While reducing the silver content, the material cost was reduced, electrode defects were decreased, and photoelectric conversion efficiency and conductivity were improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116936159B_ABST
    Figure CN116936159B_ABST
Patent Text Reader

Abstract

The invention discloses a low-silver-content solar cell low-temperature sintering type HJT silver paste and a preparation method thereof, which comprises, by weight, 50-70 parts of modified silver-coated copper powder, 11-25 parts of organic carrier, 1-3 parts of modified graphene, 0.1-0.3 parts of dispersant and 0.1-0.3 parts of thixotropic agent; the modified graphene is prepared by modifying graphene oxide with lauramide propylamine oxide; the modified silver-coated copper powder is prepared by surface modification of the silver-coated copper powder with a phenolic hydroxyl silane coupling agent; the phenolic hydroxyl silane coupling agent has a structure shown in the following formula A. The HJT silver paste provided by the invention can reduce the silver content in the silver paste and can reduce the contact resistance of the solar cell, thereby improving the photoelectric conversion efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer-based conductive materials, and in particular to a low-silver-content solar cell low-temperature sintering HJT silver paste and a preparation method thereof. Background Art

[0002] With the extreme consumption of fossil energy, the energy depletion and the increasingly serious greenhouse effect, the demand for new clean energy has become more and more urgent. As the most ideal renewable energy, solar energy has the characteristics of "inexhaustible and inexhaustible", and the use of solar energy for power generation has the advantages of environmental protection, low cost, high efficiency, and no need to consider its safety issues. At present, crystalline silicon solar cells are one of the effective devices for converting solar energy into electrical energy. Its application range is expanding from aerospace and military to people's daily life. While not generating new pollution, the reduction in cost will make solar cells more widely used.

[0003] Solar cells are semiconductor devices that can convert light energy into electrical energy. The generated electrical energy can be conducted with the help of metallized electrodes formed by sintering the electronic paste of solar cells. Among them, HJT (heterojunction) solar cells are new solar cells prepared by depositing amorphous silicon thin films on crystalline silicon. They have good passivation effects, can achieve low-temperature sintering, reduce process costs, and have high photoelectric conversion efficiency. They are currently a hot research topic for high-efficiency silicon-based solar cells.

[0004] Solar cell silver paste is the main component of solar cell electronic paste, which is mainly used to make electrodes in the production process of solar cells. With the development of the new energy industry, market competition is becoming increasingly fierce, and the price of photovoltaic modules continues to fall, resulting in increasing cost pressure on photovoltaic module manufacturers. Reducing material costs is one of the key points to reduce the manufacturing cost of photovoltaic modules. Among them, silver powder is the main cost source of HJT silver paste, and reducing the silver content in HJT silver paste is a direct and effective way to reduce the cost of HJT silver. However, in the HJT silver paste of solar cells in the prior art, as the silver content decreases, the performance of the silver paste will decrease, and the lower silver content will cause the silver powder to shrink during the sintering process of the silver paste, causing cracks and holes in the electrode, resulting in increased battery resistance and reduced photoelectric conversion efficiency.

[0005] Therefore, there is an urgent need for a low-silver-content, low-temperature sintering HJT silver paste for solar cells that can reduce the silver content in the silver paste, reduce the resistance of solar cells, and improve the photoelectric conversion efficiency. Summary of the invention

[0006] Purpose of the invention: In view of the defects of the prior art, the purpose of the present invention is to provide a low-silver content solar cell low-temperature sintering HJT silver paste and a preparation method thereof, which can reduce the silver content in the silver paste and reduce the resistance of the solar cell and improve the photoelectric conversion efficiency.

[0007] Technical solution:

[0008] A low-silver-content solar cell low-temperature sintering HJT silver paste, comprising, by weight, 50-70 parts of modified silver-coated copper powder, 11-25 parts of an organic carrier, 1-3 parts of modified graphene, 0.1-0.3 parts of a dispersant and 0.1-0.3 parts of a thixotropic agent;

[0009] The modified graphene is prepared by modifying graphene oxide with lauryl amide propyl amine oxide;

[0010] The modified silver-coated copper powder is prepared by modifying the surface of the silver-coated copper powder with a phenolic hydroxyl silane coupling agent.

[0011] Furthermore, the phenolic hydroxyl silane coupling agent has a structure as shown in the following formula A:

[0012]

[0013] In the present invention, modified silver-coated copper powder is added to replace silver powder, wherein the silver content is only 20-30wt% of conventional silver powder, and the silver content in the silver paste can be greatly reduced while maintaining the performance of the silver paste, thereby reducing the material cost.

[0014] Furthermore, the organic carrier comprises a thermosetting resin, a curing agent and a solvent; the thermosetting resin is an epoxy resin; the curing agent is selected from at least one of hexahydromethylphthalic anhydride, trimethylhexamethylenediamine, and aminoethylpiperazine; and the solvent is selected from at least one of terpineol, butyl carbitol, and butyl carbitol acetate.

[0015] Furthermore, the dispersant is selected from at least one of dimethylacetamide, sorbitan trioleate, and alkylphenol polyoxyethylene ether; and the thixotropic agent is selected from one of hydrogenated castor oil and polyamide wax.

[0016] Furthermore, the phenolic hydroxyl silane coupling agent is prepared by the following steps: adding 4-(chloromethyl)phenyltrimethoxysilane, 2-amino-1,4-dihydroxybenzene, potassium carbonate, a catalyst and an organic solvent into a reactor, heating to 85-95° C. under a protective gas environment, reacting for 18-24 hours, filtering, removing the organic solvent, washing and drying to obtain the phenolic hydroxyl silane coupling agent.

[0017] In the present invention, the surface of the silver-coated copper powder is modified by using a phenolic hydroxyl silane coupling agent. The phenolic hydroxyl structure in the phenolic hydroxyl silane coupling agent enables the silver-coated copper powder to have excellent bonding ability, and the specific surface area and tap density of the silver-coated copper powder can be effectively controlled through the large steric hindrance of the structure, so that the silver-coated copper powder has excellent dispersibility and excellent bonding ability with a battery substrate, thereby reducing the generation of defects, forming a uniform film layer after sintering, and reducing the contact resistance of the battery.

[0018] Furthermore, the mass ratio of the 4-(chloromethyl)phenyltrimethoxysilane to 2-amino-1,4-dihydroxybenzene is 2:1-1.2; and the catalyst is potassium iodide.

[0019] Furthermore, the modified graphene is prepared by the following steps:

[0020] (1) ultrasonically dispersing graphene oxide in N,N-dimethylformamide to obtain a graphene dispersion;

[0021] (2) Adding graphene dispersion and lauryl amide propyl amine oxide into a reactor, adding hydrazine hydrate after ultrasonic treatment for 30-50 minutes, stirring evenly and transferring to a reactor;

[0022] (3) heating the reaction kettle to 80-90° C., reacting for 2-3 hours, and then filtering, washing, and drying to obtain the modified graphene.

[0023] In the present invention, a small amount of modified graphene is doped, and after the modified graphene is non-covalently surface-modified with lauryl amide propylamine oxide, the dispersibility of the graphene and the compatibility with the silver paste components can be effectively improved, so that the modified graphene is evenly dispersed in the silver paste, the porosity of the silver paste can be reduced, the conductive network can be increased, the resistance can be reduced, and the conductivity and photoelectric conversion efficiency can be improved.

[0024] Furthermore, the mass ratio of the graphene oxide to lauryl amide propyl amine oxide is 1:1.5-2.5.

[0025] The method for preparing any one of the above-mentioned low-silver content solar cell low-temperature sintering HJT silver pastes comprises the following steps:

[0026] (1) adding silver-coated copper powder and tetrahydrofuran into a reactor, adding phenolic hydroxyl silane coupling agent and ethylenediamine after vibrating and dispersing, ultrasonically treating for 15-20 minutes, centrifuging and drying to obtain modified silver-coated copper powder;

[0027] (2) weighing the modified silver-coated copper powder, the organic carrier, the modified graphene, the dispersant and the thixotropic agent in proportion, adding them into a double planetary mixer, and stirring them at a speed of 100-150 rpm for 30-50 minutes to prepare a slurry;

[0028] (3) The slurry is placed in a three-roll grinder, and ground for 10-15 times at a grinding speed of 300-500 rpm and a pressure of 0.8-1 MPa, so that the average fineness of the slurry is ≤10 μm to obtain the low-silver content solar cell low-temperature sintering type HJT silver paste.

[0029] In the present invention, the silver-coated copper powder is surface-modified and doped with modified graphene by using a phenolic hydroxyl silane coupling agent, so that cracks and voids in the electrode, as well as grid line collapse and grid line breakage caused by the easy shrinkage of the silver powder during the sintering of a slurry with a low silver content can be reduced, thereby reducing the series resistance of the electrode and improving the photoelectric conversion efficiency of the solar cell.

[0030] Furthermore, in the step (1), the silver content of the silver-coated copper powder is 20-30wt%, and the mass ratio of the silver-coated copper powder to the phenolic hydroxyl silane coupling agent is 1:0.2-0.3; and the sintering temperature of the low-silver-content solar cell low-temperature sintering type HJT silver paste is 250-350°C.

[0031] Beneficial effects:

[0032] (1) The present invention provides a low-silver-content solar cell low-temperature sintering HJT silver paste in which modified silver-coated copper powder is added to replace silver powder, wherein the silver content is only 20-30wt% of conventional silver powder. The silver content in the silver paste can be greatly reduced while maintaining the performance of the silver paste, thereby reducing material costs.

[0033] (2) In the low-silver content solar cell low-temperature sintering type HJT silver paste provided by the present invention, the silver-coated copper powder is surface modified by a phenolic hydroxyl silane coupling agent. The phenolic hydroxyl structure in the phenolic hydroxyl silane coupling agent enables it to have excellent bonding ability with the silver-coated copper powder, and through the large steric hindrance of its structure, the specific surface area and tap density of the silver-coated copper powder can be effectively controlled, thereby making the silver-coated copper powder have excellent dispersibility and excellent bonding ability with the battery substrate, reducing the generation of defects, forming a uniform film layer after sintering, and reducing the battery resistance.

[0034] (3) The low-silver-content solar cell low-temperature sintering type HJT silver paste provided by the present invention contains a small amount of modified graphene doped in it. After the modified graphene is non-covalently surface-modified with lauryl amide propylamine oxide, the dispersibility and compatibility of the graphene with the silver paste components can be effectively improved, so that the modified graphene is evenly dispersed in the silver paste, which can reduce the porosity of the silver paste, increase the conductive network, reduce the resistance, and improve the conductivity and photoelectric conversion efficiency.

[0035] (4) In the low-silver content solar cell low-temperature sintering HJT silver paste provided by the present invention, the silver-coated copper powder is surface modified and doped with modified graphene by using a phenolic hydroxyl silane coupling agent, which can reduce the phenomenon of cracks and voids in the electrode, as well as grid line collapse and grid line breakage caused by the easy shrinkage of silver powder during sintering of the low-silver content paste, thereby reducing the series resistance of the electrode and improving the photoelectric conversion efficiency of the solar cell. DETAILED DESCRIPTION

[0036] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.

[0037] The commercially available HJT silver paste is YBS-HJT-Ag85 purchased from Yibo Strontium (Guangzhou) Nano Technology Co., Ltd.; the silver-coated copper powder is S-U315 purchased from Shenzhen Xiat Technology Co., Ltd.; the graphene oxide is 796034 purchased from Merck; the commercially available silver powder is high-purity silver powder purchased from Nangong Xiangfan Alloy Materials Co., Ltd.; the remaining reagents and equipment are conventional reagents and equipment in this technical field.

[0038] Preparation of phenolic hydroxy silane coupling agent

[0039] The phenolic hydroxy silane coupling agent was prepared by the following steps:

[0040] In a round-bottom flask, 60 g of 4-(chloromethyl)phenyltrimethoxysilane, 35 g of 2-amino-1,4-dihydroxybenzene, 90 g of potassium carbonate, 3 g of potassium iodide and 300 mL of anhydrous toluene were added, and heated to 90° C. under nitrogen protection. After reacting for 24 hours, the phenolic hydroxy silane coupling agent was obtained by suction filtration, removal of organic solvent, washing and drying.

[0041] Mass spectrum data of the product: The product was analyzed by LC-MS, and the m / z of the product was 335.12 (100.0%), 336.16 (24.0%), and 337.13 (6.2%).

[0042] Modified graphene preparation

[0043] The modified graphene was prepared by the following steps:

[0044] (1) ultrasonically dispersing 100 mg of graphene oxide in 100 mL of N,N-dimethylformamide to prepare a graphene dispersion;

[0045] (2) In the reactor, 100 mL of graphene dispersion and 200 mg of lauryl amide propyl amine oxide were added, and 1 mL of hydrazine hydrate was added after 150 W ultrasonic treatment for 40 minutes, and the mixture was stirred evenly and then transferred to the reactor;

[0046] (3) The reactor was heated to 90° C., reacted for 3 hours, and then filtered, washed, and dried to obtain modified graphene.

[0047] Example 1

[0048] The low-silver content HJT silver paste for solar cells is prepared by the following steps:

[0049] (1) In a centrifuge tube, 10 g of silver-coated copper powder and 30 mL of tetrahydrofuran were added, and after vibrating and dispersing, 2 g of phenolic hydroxyl silane coupling agent and 20 mL of ethylenediamine were added. After ultrasonic treatment at 100 W for 20 minutes, the mixture was centrifuged and dried to obtain modified silver-coated copper powder;

[0050] (2) 70 parts of modified silver-coated copper powder, 10 parts of bisphenol A epoxy resin, 14 parts of butyl carbitol, 1 part of trimethylhexamethylenediamine, 3 parts of modified graphene, 0.3 parts of dimethylacetamide and 0.3 parts of hydrogenated castor oil were weighed in proportion and added into a double planetary mixer, and stirred at a speed of 150 rpm for 40 minutes to prepare a slurry;

[0051] (3) The slurry is placed in a three-roller grinder, and ground 15 times at a grinding speed of 500 rpm and a pressure of 1 MPa, so that the average fineness of the slurry is ≤10 μm to obtain the low-silver content solar cell low-temperature sintering type HJT silver paste.

[0052] Example 2

[0053] The method is basically the same as Example 1, except that the components are changed to 60 parts of modified silver-coated copper powder, 6 parts of bisphenol A epoxy resin, 8 parts of pine alcohol, 1 part of trimethylhexamethylenediamine, 2 parts of modified graphene, 0.3 parts of sorbitan trioleate and 0.3 parts of polyamide wax in terms of weight percentage; the sintering temperature of the obtained low-silver content solar cell low-temperature sintering type HJT silver paste is 325°C.

[0054] Example 3

[0055] The invention is basically the same as Example 1, except that the components are changed to 50 parts of modified silver-coated copper powder, 5.5 parts of bisphenol F epoxy resin, 7 parts of butyl carbitol, 0.5 parts of aminoethylpiperazine, 1 part of modified graphene, 0.3 parts of alkylphenol polyoxyethylene ether and 0.3 parts of polyamide wax in terms of weight proportion; the sintering temperature of the obtained low-silver-content solar cell low-temperature sintering type HJT silver paste is 325°C.

[0056] Comparative Example 1

[0057] Commercially available HJT silver paste.

[0058] Comparative Example 2

[0059] The method is basically the same as Example 1, except that step (1) is not performed, and the modified silver-coated copper powder in step (2) is replaced with an equal amount of commercially available silver powder.

[0060] Performance Testing

[0061] Silver content detection: The silver content in the silver pastes prepared in Examples 1-3 and Comparative Examples 1-6 was detected.

[0062] The HJT silver pastes prepared in Examples 1-3 and Comparative Examples 1-6 were printed on the front surfaces of N-type PERC cells for testing.

[0063] Contact resistance detection: The commonly used TLM (transmission line model) is used to detect the contact resistance of the battery prepared above.

[0064] Photoelectric conversion efficiency detection: Use TMC-PV1A solar cell tester to detect IV curve and detect the photoelectric conversion efficiency of the above-prepared battery.

[0065] Silver content (wt%) Contact resistance(Ω) Photoelectric conversion efficiency (%) Example 1 18.2 1.23 23.31 Example 2 18.5 1.21 23.32 Example 3 17.9 1.23 23.32 Comparative Example 1 82.3 1.29 23.17 Comparative Example 2 72.3 1.23 23.29

[0066] According to the comparison of the test results of Examples 1-3 with those of Comparative Examples 1 and 2, it can be seen that the low-silver-content solar cell low-temperature sintering HJT silver paste provided by the present invention can also achieve a contact resistance similar to that when commercially available silver powder is used alone while reducing the silver content, and the solar cell still has excellent photoelectric conversion efficiency.

[0067] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A low-silver-content solar cell low-temperature sintering HJT silver paste, characterized in that: The invention comprises, by weight, 50-70 parts of modified silver-coated copper powder, 11-25 parts of an organic carrier, 1-3 parts of modified graphene, 0.1-0.3 parts of a dispersant and 0.1-0.3 parts of a thixotropic agent; The modified graphene is prepared by modifying graphene oxide with lauryl amide propyl amine oxide; The mass ratio of graphene oxide to lauryl amide propyl amine oxide is 1:1.5-2.5; The modified silver-coated copper powder is prepared by the following steps: In a reactor, silver-coated copper powder and tetrahydrofuran are added, phenolic hydroxyl silane coupling agent and ethylenediamine are added after vibrating and dispersing, and after ultrasonic treatment for 15-20 minutes, centrifugation and drying are performed to obtain modified silver-coated copper powder; The silver content of the silver-coated copper powder is 20-30wt%, and the mass ratio of the silver-coated copper powder to the phenolic hydroxyl silane coupling agent is 1:0.2-0.3; The phenolic hydroxyl silane coupling agent has a structure as shown in the following formula A: 。 2. The low-silver-content solar cell low-temperature sintering HJT silver paste according to claim 1, characterized in that: The organic carrier comprises a thermosetting resin, a curing agent and a solvent; the thermosetting resin is an epoxy resin; the curing agent is selected from at least one of hexahydromethylphthalic anhydride, trimethylhexamethylenediamine and aminoethylpiperazine; and the solvent is selected from at least one of terpineol, butyl carbitol and butyl carbitol acetate.

3. The low-silver-content solar cell low-temperature sintering HJT silver paste according to claim 1, characterized in that: The dispersant is selected from at least one of dimethylacetamide, sorbitan trioleate, and alkylphenol polyoxyethylene ether; and the thixotropic agent is selected from one of hydrogenated castor oil and polyamide wax.

4. The low-silver-content solar cell low-temperature sintering HJT silver paste according to claim 1, characterized in that: The phenolic hydroxy silane coupling agent is prepared by the following steps: adding 4-(chloromethyl)phenyltrimethoxysilane, 2-amino-1,4-dihydroxybenzene, potassium carbonate, a catalyst and an organic solvent into a reactor, heating to 85-95° C. under a protective gas environment, reacting for 18-24 hours, filtering, removing the organic solvent, washing and drying to obtain the phenolic hydroxy silane coupling agent.

5. The low-temperature sintering HJT silver paste for solar cells with low silver content according to claim 4, characterized in that: The mass ratio of the 4-(chloromethyl)phenyltrimethoxysilane to 2-amino-1,4-dihydroxybenzene is 2:1-1.2; and the catalyst is potassium iodide.

6. The low-silver-content solar cell low-temperature sintering HJT silver paste according to claim 1, characterized in that: The modified graphene is prepared by the following steps: (1) ultrasonically dispersing graphene oxide in N,N-dimethylformamide to obtain a graphene dispersion; (2) Add graphene dispersion and lauryl amide propyl amine oxide into the reactor, add hydrazine hydrate after ultrasonic treatment for 30-50 minutes, stir evenly and transfer to the reactor; (3) The reaction kettle is heated to 80-90° C., reacted for 2-3 hours, and then filtered, washed, and dried to obtain the modified graphene.

7. The method for preparing the low-silver-content low-temperature sintering HJT silver paste for solar cells according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Weighing modified silver-coated copper powder, organic carrier, modified graphene, dispersant and thixotropic agent in proportion, adding them into a double planetary mixer, stirring at a speed of 100-150 rpm for 30-50 minutes to prepare a slurry; (2) The slurry is placed in a three-roll mill and ground for 10-15 times at a grinding speed of 300-500 rpm and a pressure of 0.8-1 MPa, so that the average fineness of the slurry is ≤10 μm to obtain the low-silver content solar cell low-temperature sintering type HJT silver paste.

8. The method for preparing a low-silver-content solar cell low-temperature sintering HJT silver paste according to claim 7, characterized in that: The sintering temperature of the low-silver-content solar cell low-temperature sintering HJT silver paste is 250-350°C.

Citation Information

Patent Citations

  • Solar cell front side silver slurry doped with modified graphene and manufacture method therefor

    CN105845198A

  • Silane coupling agent modified silver-coated copper powder heterojunction battery silver paste and preparation method thereof

    CN116206799A